The Anglican Attack on Hobbes in Paris, 1651 - Raylor, Timothy (The historical journal, 2010)
About the circumstances surrounding Hobbes's dismissal from Charles's court and his subsequent departure from Paris at the end of 1651 we know little. While recent scholarship has clarified the broad outline of events, fresh evidence allows us to add some detail, showing that Leviathan was attacked in a sermon delivered by Richard Steward in the Anglican chapel of Sir Richard Browne, thus confirming Hobbes's claim for the involvement of the Anglican establishment in engineering his dismissal from court and giving us a slightly clearer sense of the source and character of the move against him.